KEPUASAN DAN LOYALITAS PELANGGAN HYPERMARKET: LITERATUR REVIEW (Manajemen & Bisnis Jurnal, 2021)
Previous literature reviews have explored the relationship between customer satisfaction and loyalty. The purpose of reviewing this scope is to map existing studies that assess the influence of customer satisfaction on customer loyalty. The main steps in scoping are: (1) defining the research questions; (2) identify relevant studies; (3) research selection; ( ) cartographic data, and (5) compile, summarize, and report results, using multiple national assessments. The results of the scope review show that most studies recognize that customer satisfaction affects customer loyalty. However, as Taylor and Gary Hunter (2003) have argued, Cristobal. E, et al (2007) customer satisfaction does not affect customer loyalty.